Gestão de relacionamento para criação de valor em uma instituição de ensino - Grandolfo, Daniel Jankops (2019)
This study adresses a work performed in a higher education institution (HEI) with the main objective of promote value proposal expansion in the relationship with students. As a means to achieve this goal, To accomplish this goal, we seek to achieve the specific objectives of: proposing actions to increase the efficiency of the service process and student satisfaction, reducing the incidence of complaints, identifying means and proposing solutions to improve student relationship management and create value for the institution, its students and other stakeholders. It is an interventionist proposal, accepted by HEI. Initially, we describe the steps already taken so far and then the future steps to be taken. Part of the intervention that has already been carried out includes the steps of defining the task force responsible for required actions, interactions and analyzes dedicated to understanding the problem, searching for technological solutions available in the market and contacts with potential suppliers, developing, detailing and presenting the project to internal decision-making bodies. After their approval, the tool was acquired and is being implemented according to the established schedule. Tests performed in the initial phase of implementation indicate potential gains in quality of service to the target audience. The ongoing project is characterized as a significant change in the institutional practices of relationship with its target audiences, constituting innovative and replicable action in other similar organizations, which also deal with the characteristic complexity of managing the relationship with their audiences.